Collaborative R&D and European Industry - Van Der Meer, Wim
Wim van der Meer, Guus Trommelen, Jan Vleggaar and Peter Vriezen present the findings of an EIRMA study.
Rapid technological change and globalization are driving R&D collaboration. An EIRMA study adds details.
A recent questionnaire on collaborative R&D reveals current thinking and actual experiences of a large fraction of the European R&D-intensive industry. There is general agreement on the main driving forces for collaborative R&D; namely, rapid technological change, globally accessing technology and more demanding customers. However, the perspective from various organizational layers on specific issues may differ considerably. A large majority of the corporate representatives expect an increase in volume. This is not the case among the business unit people. As the primary reason for collaboration, the corporate layer cited new product development, while environmental problems led the responses from business units. The strategic integration of collaborative R&D appears to be less than that of other R&D. Simple measures like formulating a policy and strategy for collaborative R&D, together with attention to good project management practices, enhance the chances for a successful collaboration considerably.
Keywords: Collaborative R&D.